DFT study of salicylaldehyde semicarbazone derivatives interaction with copper and the effect of aminic substituent - Tan, Shiow Jin (2013)
The effect of aminic substituent on the stability of conformers and the bond nature of copper complexation of N-alkyl, N-aryl substituted salicylaldehyde semicarbazone (H2ssc) were studied using DFT B3LYP method, including the natural bond orbital (NBO) analysis. We found three stable conformers for N-alkyl, N-aryl H2ssc: the trans(NN, CN), cis(NN)–trans(CN) and trans(NN)–cis(CN) conformer. The DFT calculations indicate that the N-alkyl and N-aryl substitution affects the relative stability among the H2ssc conformers: contrast to H2ssc (most stable confirmer is trans(NN)–cis(CN)), the trans(NN, CN) conformer is the most stable conformation of the substituted H2ssc. From NBO analysis, besides ionic interaction, the coordination of ligands to copper also include considerably strong covalent property: by n(ligand atom) → 4s(copper) donor–acceptor interaction the ligand forms a strong covalent interaction with copper. The NBO analysis also reveals that complexation with copper atom decomposes the conjugation system along the ligand molecular plane.